2016
DOI: 10.1093/nar/gkw054
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a conserved 5′-dRP lyase activity in bacterial DNA repair ligase D and its potential role in base excision repair

Abstract: Bacillus subtilis is one of the bacterial members provided with a nonhomologous end joining (NHEJ) system constituted by the DNA-binding Ku homodimer that recruits the ATP-dependent DNA Ligase D (BsuLigD) to the double-stranded DNA breaks (DSBs) ends. BsuLigD has inherent polymerization and ligase activities that allow it to fill the short gaps that can arise after realignment of the broken ends and to seal the resulting nicks, contributing to genome stability during the stationary phase and germination of spo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 64 publications
1
25
0
Order By: Relevance
“…However, no clear trend toward the co-occurrence of these two “variable” genes can be noticed in the 38 analysed genomes. In B. subtilis , the recent involvement of LigD Bsub and Ku Bsub in base excision repair along with their major role in NHEJ supports the third hypothesis (de Ory et al, 2014, 2016). …”
Section: Discussionmentioning
confidence: 62%
“…However, no clear trend toward the co-occurrence of these two “variable” genes can be noticed in the 38 analysed genomes. In B. subtilis , the recent involvement of LigD Bsub and Ku Bsub in base excision repair along with their major role in NHEJ supports the third hypothesis (de Ory et al, 2014, 2016). …”
Section: Discussionmentioning
confidence: 62%
“…Together, these findings establish that both LigC and LigD-dependent complexes contribute significantly to the repair of lesions produced by oxidative damage during stationary phase in mycobacteria. Notably, Ory et al 44 reported recently that Bacillus subtilis LigD possesses dRP-ase activity in vitro supporting this proposed role in excision repair. Further studies are required to define the exact nature of the oxidative lesions that these Prim-Pol pathways process in vivo and uncover the overlap and “cross-talk” that occurs between these, and other, stationary phase DNA repair pathways in mycobacteria.…”
Section: Discussionmentioning
confidence: 77%
“…The region of Pa-LigD gene encoding PolDom (residues 533-840; [43]) was amplified by PCR using as substrate the recombinant plasmid pET16-PaLigD [44], a sense strand primer that introduced an NdeI restriction site substituting the original codon for Arg532 by a methionine codon, and an antisense primer that introduced a BamHI site. Both, plasmid pET16 and the PCR products were double digested with NdeI and BamHI and further ligated to give rise to plasmid pET16-Pa-PolDom.…”
Section: Expression and Purification Of Recombinant Pa-poldommentioning
confidence: 99%